Desmopressin testing in von Willebrand disease: Lowering the burden. Issue 6 (26th September 2022) - Heijdra, Jessica M.; Atiq, Ferdows; Al Arashi, Wala; Kieboom, Quincy; Wuijster, Esmee; Meijer, Karina; Kruip, Marieke J. H. A.; Leebeek, Frank W. G.; Cnossen, Marjon H.
Abstract: Background: Individuals with von Willebrand disease (VWD) require desmopressin testing because of interindividual response differences. However, testing is burdensome, while not all patients may need extensive testing. Objectives: To provide von Willebrand factor (VWF) cutoffs that predict desmopressin nonresponse and thereby identify individuals who do not need extensive testing in a retrospective cohort. We validated these cutoffs in a prospective cohort. Patients and Methods: We included 376 patients (Type 1 VWD with VWF activity [VWF:Act] <0.30 IU/ml: n  = 112; with VWF:Act 0.30–0.50 IU/ml: n  = 206; Type 2 VWD: n  = 58; ages, 5–76 years) from January 2000 to July 2020. We collected VWF:Act and factor VIII activity (FVIII:C) at baseline and several time points after desmopressin (T1–T6). We defined response as VWF:Act and FVIII:C 0.50 IU/ml or greater at T1 and T4. We compared VWF:Act and FVIII:C distribution (historically lowest level, baseline, and T1) between responders and nonresponders and determined cutoffs discriminating between these groups. Results were validated in a group of 30 individuals. Results: All individuals with Type 1 VWD and Type 2 VWD, respectively, with baseline VWF:Act 0.34 IU/ml or greater or 0.28 IU/ml or greater were responders. In individuals with T1 VWF:Act ≥0.89 IU/ml (Type 1 VWD) or T1 VWF:Act 1.10 IU/ml or greater (Type 2 VWD), response remained at T4. Conclusion: Desmopressin testing is not needed when lowest historical VWF:Act is 0.30 IU/ml or greater. In patients with Type 1 VWD who require testing, measurements after T1 are often not needed. In patients with Type 2 VWD who require testing, we advise performing T1 and T4 measurements.